2019
DOI: 10.5194/bg-2019-119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ocean carbonate system variability in the North Atlantic Subpolar surface water (1993–2017)

Abstract: The North Atlantic is one of the major sinks for anthropogenic CO2. In this study, we investigate the evolution of CO2 uptake and ocean acidification in the North Atlantic Subpolar Gyre (50°N-64°N) using repeated observations collected over the last three decades in the framework of the long-term monitoring program SURATLANT (SURveillance de l'ATLANTique). Data obtained between 1993 and 1997 suggest an important reduction in the capacity of the ocean to absorb CO2 from the atmosphere during summer, due to a ra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
4
2
0
Order By: Relevance
“…Located outside the main ocean currents of the NA, both stations similarly undergo the warming and longterm salinification observed during the last decades 23,43,46,47 . The IRM-TS shows a long-term surface warming of 0.063 ± 0.005 (Table 2), which is consistent with those shown recently by Leseurre et al 25 (0.05 ± 0.01 C yr −1 between 1993 and 2017) in the northern Irminger Sea. The lower warming trend shown by these authors is due to the recent cooling period between 2008 and 2017 (− 0.05 ± 0.01 per year), which was also observed by Frob et al 27 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Located outside the main ocean currents of the NA, both stations similarly undergo the warming and longterm salinification observed during the last decades 23,43,46,47 . The IRM-TS shows a long-term surface warming of 0.063 ± 0.005 (Table 2), which is consistent with those shown recently by Leseurre et al 25 (0.05 ± 0.01 C yr −1 between 1993 and 2017) in the northern Irminger Sea. The lower warming trend shown by these authors is due to the recent cooling period between 2008 and 2017 (− 0.05 ± 0.01 per year), which was also observed by Frob et al 27 .…”
Section: Discussionsupporting
confidence: 91%
“…The acidification trends found here in the surface layer at the IS-TS and IRM-TS are within the values observed in other time series collected by Bates and others 6 . The trend of pH T decrease at the IRM-TS (1.70 ± 0.19 10 −3 yr −1 ) is very close to that determined by Leseurre et al 25 in the northern Irminger Sea (1.6 ± 0.1 10 −3 yr −1 using winter data) and to that determined by Garcia-Ibañez et al 14 in the same basin from hydrographic sections of the A-25 GOSHIP line from 1991 to 2015 (1.8 ± 0.1 10 −3 yr −1 ), while Vázquez-Rodríguez et al 11 obtained the same trend between 1981 and 2008 for the same section. Lauvset et al 50 found a similar trend of 2.0 ± 0.4 10 −3 yr −1 for the North Atlantic subpolar seasonally stratified (NA-SPSS) biome from 1991 to 2011.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations